Soybean balanced the growth and defense in response to SMV infection under different light intensities - Shang, Jing; Zhao, Lu-Ping; Yang, Xin-Miao; Qi, Xiao-Li; Yu, Jin-Feng; Du, Jun-Bo; Li, Kai; He, Cheng-Shan; Wang, Wen-Ming; Yang, Wen-Yu (Frontiers in Plant Science, 2023)
Light is essential for the growth and defense of soybean. It is not clear how soybeans adjust their defenses to different light environments with different cropping patterns. The mechanism of soybean response to Soybean mosaic virus infection under different light intensity was analyzed by RNA-seq sequencing method. Enrichment analysis illustrated that most defense-related genes were down-regulated under dark and shade, and up-regulated under highlight and normal light. Soybean can resist SMV infection mainly by activating salicylic acid signaling pathway. Light is essential for activating salicylic acid defense signaling pathways. With the increase of light intensity, the oxidative damage of soybean leaves was aggravated, which promoted the infection of virus. When light was insufficient, the growth of soybean was weak, and the plant-pathogen interaction pathway, MAPK pathway and hormone defense pathway in infected soybean was inhibited to varying degrees. Under strong light, some defense genes in infected soybean were down-regulated to reduce the degree of oxidative damage. The expression of differentially expressed genes was verified by real-time fluorescence quantitative RT-PCR. In order to adapt to the change of light intensity, soybean balanced allocation of resources between growth and defense through a series of gene expression regulation. The results of this study will provide a theoretical basis for the research of SMV resistance in intercropping soybean.